EVALUASI IMPLEMENTASI KEBIJAKAN NO. 12 TAHUN 2012 TENTANG TUNTUTAN PENGELOLAAN KURIKULUM - Dwi Deswary (Universitas Negeri Jakarta, 2017)
This study aims to determine (1) The results of the input evaluation; (2) The results of the evaluation process; and (3) The results of the product evaluation on the policy implementation of Act 12 of the year 2012 on the Program Study of Education Management, Postgraduate Program, University State of Jakarta (UNJ). The research method was a qualitative evaluation approach. Data collected by conducting an analysis of document-based curriculum KKNI to determine the success of the implementation by stages conducted at Postgraduate Program Study of Education Management. The data were analysed descriptively and meaning on any research findings conducted qualitatively. Stages of meaning carried out through the following stages: (1) Data Collection; (2) Data Reduction; and (3) Data Display. Based on the results of input evaluation which performed on the curriculum document, known that the preparation Program Study based on curriculum KKNI of Education Management Postgraduate Program is equipped with a clear legal basis, the formulation of goals and objectives. In the aspect of supporting resources for curriculum development, Progam Study has form data analysis of curriculum results, planned programs and implementation strategies. In the process, learning strategies are divided into two approaches, namely direct and indirect approaches. In evaluating, the results are more geared towards the achievement of the program on implementation of policies based on curriculum KKNI in Postgraduate Program Study of Education Management by a predetermined time phase, namely the achievement during the short-term period (1 to 2 years).